Natural frequency analysis of imperfect GNPRN conical shell, cylindrical shell, and annular plate structures resting on Winkler-Pasternak Foundations under arbitrary boundary conditions - Sobhani, Emad; Avcar, Mehmet (Engineering analysis with boundary elements, 2022)
The goal of the present research is to examine the Natural Frequencies (NFs) of perfect and imperfect Graphene Nanoplatelet Reinforced Nanocomposite (GNPRN) structures of revolution (conical and cylindrical shells and annular plate structures) resting on elastic foundations under general boundary conditions (BCs). The graphene nanoplatelet material is implemented to compose the nanocomposite enhanced by a polymeric matrix including porosities. The springs technique is applied to define the general BCs of GNPRN structures of revolution. Elastic foundations are described by two parameters, i.e., Winkler-Pasternak Foundations (WPFs). Additionally, Donnell's hypothesis and first-order shear deformation theory (FSDT) are employed to figure out the primary formulations associated with the GNPRN structures of revolution. In contrast, the equations of motion are found using Hamilton's principle. Then the equations of motion are then discretized using the well-known Generalized Differential Quadrature Method (GDQM). Next, the standard eigenvalue solution is assigned to obtain the NFs of the perfect/imperfect GNPRN structures of revolution. Finally, various benchmarks are addressed to verify the approach suggested for evaluating the NFs of the perfect/imperfect GNPRN structures of revolution. Furthermore, several novel examples highlight the effects of the change in geometrical and material properties, arbitrary boundary conditions, and WPFs on the NFs of the perfect/imperfect GNPRN structures of revolution.